2005
DOI: 10.4315/0362-028x-68.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Sigma Factor σB Is Not Essential for Listeria monocytogenes Surface Attachment

Abstract: Listeria monocytogenes is a foodborne pathogen frequently isolated from the food processing environment. Multiple lines of evidence suggested a possible role for the L. monocytogenes alternative transcription factor sigma B (sigmaB) in surface attachment and biofilm formation. Therefore, through plate count and microscopic techniques, the L. monocytogenes 10403S strain and an otherwise isogenic deltasigB strain were tested for attachment to stainless steel. Analysis of microscopic images revealed that after 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Flint et al [32] found that cultures of Streptococcus thermophilus and Bacillus cereus attached to stainless steel in less than 60 s and subsequent washing with distilled water proved ineffective in removing attached cells. Schwab et al [95] noted that numbers of L. monocytogenes attached to stainless steel were essentially the same either after 5 min or 24 h incubation. Butler et al [15] reported similar findings with meat surfaces, noting considerable attachment of bacterial cells taking place in the first minute of contact, though small increases were also seen over time.…”
Section: Attachmentmentioning
confidence: 98%
“…Flint et al [32] found that cultures of Streptococcus thermophilus and Bacillus cereus attached to stainless steel in less than 60 s and subsequent washing with distilled water proved ineffective in removing attached cells. Schwab et al [95] noted that numbers of L. monocytogenes attached to stainless steel were essentially the same either after 5 min or 24 h incubation. Butler et al [15] reported similar findings with meat surfaces, noting considerable attachment of bacterial cells taking place in the first minute of contact, though small increases were also seen over time.…”
Section: Attachmentmentioning
confidence: 98%
“…Previously, a role for stress response sigma factors in the resistance of Pseudomonas aeruginosa biofilms to disinfectants has been shown (11). For L. monocytogenes, the stress response sigma factor SigB appeared not to be essential for attachment to stainless steel surfaces (39). So far, little is known on the activation and function of stress resistance mechanisms in L. monocytogenes biofilm formation and the resistance of biofilms to disinfectants.…”
mentioning
confidence: 99%
“…It has been demonstrated that both temperature sensing and chemical components of the extracellular environment play important roles in regulating the expression of the PrfA regulon (4,31,40). Additionally, the transcription of a subset of L. monocytogenes virulence genes seems to be regulated by a network that can include activation by both PrfA and sigma B (33,41,58) and interplay between PrfA and sigma B has been suggested (40).…”
mentioning
confidence: 99%